Controle judicial de sustentabilidade das decisões administrativas - Moreira, Rafael Martins Costa (2016)
This dissertation initially analyzes new trends in Public Administration and Administrative Law. It then presents a succinct study of decision theory in general, its applicability to administrative decisions, the administrative activity proceduralization, and, finally, it is proposed a concept of administrative decision. After referring to the notions of discretion and binding, its place in public decisions and outlining the features of the new discretion, this work deals with the legal and factual motivation of administrative decisions: the difference between reason and motivation, the main grounds for the requirement of motivation and valid motivation requirements. The text also deepens the study on the sustainability principle and establishes the mandatory observance of sustainable choices by the public authorities and its duty of intertemporal motivation. After settling these points, the dissertation focuses on the judicial review of sustainability of administrative decisions. Firstly, it is presented an explanation of the control of the Public Administration as a whole, which is then specified through judicial review: its concept, rationale, scope, possibilities and limits. References are made to the progress of judicial control, the importance of the proportionality principle applicable to administrative decisions and the interpretation also based on the consequences, especially for the control of motivation and the deference principle, in brief comparison to the US Law and a proposal for the Brazilian Law system. It also approaches the effectiveness of judicial protection in regard to relations in the Public Administration. Finally, it is undertaken an analysis of the application of the concepts and tools developed for the appreciation of the parameters for the judicial review of sustainability of public procurement, regulation, and the timely use of prevention and precautionary measures that have been or should have been taken by the Public Administration.